Simple high-performance liquid chromatographic assay for the determination of ciprofloxacin in human plasma with ultraviolet detection - Maya, MT (2015)
A simple high-performance liquid chromatographic method is described for the quantitative analysis of ciprofloxacin in human plasma. Following protein precipitation from plasma by means of 6% perchloric acid, the upper layer which contains the analyte and the internal standard lomefloxacin, was analysed on a reverse phase column LiChrospher(R) 60 RP-select B (5 mum) (EcoCART(R) 125-3) with ultraviolet detection at 280 nm. The mobile phase was acetic acid 5%-methanol-acetonitrile (90:5:5, v/v/v). The assay was linear for ciprofloxacin over the concentration range of 0.050 to 6.00 mug ml(-1). The limit of quantification (LOQ) was 0.050 mug ml(-1). The method was successfully applied to a bioavailability study with five different ciprofloxacin formulations. (C) 2001 Elsevier Science B.V. All rights reserved.